Where are the post-communist allotment gardens heading? (Focus point on the Czech Republic) - Barbora, Duží; Tóth, Attila; Vávra, Jan; Supuka, Ján (Università di Torino, 2018)
This paper provides an excursion to the urban allotment gardens’ specifics in a country located in the Central and Eastern Europe (CEE). The paper introduces briefly the key aspects of historical overview of allotments in former Czechoslovakia and defines significant periods which influenced urban gardening and the society in general. We capture the main characteristics prevailing in the communist regime and consequent changes after 1989, and we also discuss diverse aspects of its decline in the Czech Republic since then. Further, we indicate contemporary trends and challenges for the future of urban allotment gardening within the context of urban and food planning. In the post-communist development we revealed some significant aspects. Radical socio-economic changes after 1989 caused shrinkage of their significance in general. Consequently, the process of looking for their new position and the role in cities is taking place. New challenges for renovation of relation among food, gardening, urban planning and life in cities arise.
Kam směřují post-komunistické zahrádkové kolonie (zaostřeno na Českou republiku)
Keywords: urban gardening; allotment gardens; Czech Republic; městské zahradničení; zahrádkové kolonie; Česká republika